Octopus-Inspired Self-Adaptive Hydrogel Gripper Capable of Manipulating Ultra-Soft Objects - Wang, Yixian; Liu, Desheng; Hu, Danli; Wang, Chao; Li, Zonggang; Wu, Jiayu; Jiang, Pan; Yang, Xingxing; Bai, Changcheng; Ji, Zhongying; Jia, Xin; Wang, Xiaolong (Nano-Micro Letters, 2025)
Octopuses, due to their flexible arms, marvelous adaptability, and powerful suckers, are able to effortlessly grasp and disengage various objects in the marine surrounding without causing devastation. However, manipulating delicate objects such as soft and fragile foods underwater require gentle contact and stable adhesion, which poses a serious challenge to now available soft grippers. Inspired by the sucker infundibulum structure and flexible tentacles of octopus, herein we developed a hydraulically actuated hydrogel soft gripper with adaptive maneuverability by coupling multiple hydrogen bond-mediated supramolecular hydrogels and vat polymerization three-dimensional printing, in which hydrogel bionic sucker is composed of a tunable curvature membrane, a negative pressure cavity, and a pneumatic chamber. The design of the sucker structure with the alterable curvature membrane is conducive to realize the reliable and gentle switchable adhesion of the hydrogel soft gripper. As a proof-of-concept, the adaptive hydrogel soft gripper is capable of implement diversified underwater tasks, including gingerly grasping fragile foods like egg yolks and tofu, as well as underwater robots and vehicles that station-keeping and crawling based on switchable adhesion. This study therefore provides a transformative strategy for the design of novel soft grippers that will render promising utilities for underwater exploration soft robotics. Highlights: 1 3D printable supramolecular hydrogels with tunable mechanical properties and stiffness adaptability were enabled by strong and weak H-bonding cooperative interactions and microphase separation. 2 Sucker structure with an alterable membrane was designed and fabricated with 3D printing to realize reliable and gentle switchable adhesion. 3 Octopus-inspired hydrogel gripper that is capable of delicately handling ultra-soft underwater objects in the form of nondestructive surface release was achieved.